Using cloud technologies to check and record programming tasks - V. V. Lazoryk; V. M. Chernov (Academy of Cognitive and Natural Sciences, 2013)
The rapid development of hardware and software and the bandwidth of telecommunications networks has provided extraordinary opportunities in the use of cloud technology in many areas of life, especially in education. For example, there are many Internet resources that offer peculiar web-based software development environments (IDEs). Such IDEs allow storing the source codes of programs, debugging them, compiling and executing them. Intensification of the learning process stimulates the search for new approaches to teaching disciplines, creating new and using ready-made software to support the learning process at a high level. At the same time, an important role in the study of programming-related disciplines is played by automated information systems of verification of solutions and accounting of the results of the verification.